2022
DOI: 10.1186/s12916-022-02440-y
|View full text |Cite
|
Sign up to set email alerts
|

Mammography screening is associated with more favourable breast cancer tumour characteristics and better overall survival: case-only analysis of 3739 Asian breast cancer patients

Abstract: Background Early detection of breast cancer (BC) through mammography screening (MAM) is known to reduce mortality. We examined the differential effect that mammography has on BC characteristics and overall survival and the sociodemographic determinants of MAM utilization in a multi-ethnic Asian population. Methods This study included 3739 BC patients from the Singapore Breast Cancer Cohort (2010–2018). Self-reported sociodemographic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Singapore is the first country in Asia to launch a widespread, population-based organised mammography screening programme in 2002 [ 6 ]. However, the consistently low participation rate (<40%) is far from the ideal minimum of 70% required to see substantial mortality reduction benefits [ 7 , 8 , 35 ]. Our eight focus group discussions eliciting opinions from 54 women without a history of breast cancer revealed no novel barriers and motivations to attending screening mammography in Singapore.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Singapore is the first country in Asia to launch a widespread, population-based organised mammography screening programme in 2002 [ 6 ]. However, the consistently low participation rate (<40%) is far from the ideal minimum of 70% required to see substantial mortality reduction benefits [ 7 , 8 , 35 ]. Our eight focus group discussions eliciting opinions from 54 women without a history of breast cancer revealed no novel barriers and motivations to attending screening mammography in Singapore.…”
Section: Discussionmentioning
confidence: 99%
“…Our eight focus group discussions eliciting opinions from 54 women without a history of breast cancer revealed no novel barriers and motivations to attending screening mammography in Singapore. Misconceptions about screening, lack of perceived breast cancer risk, perceived efficacy of mammography to save lives, physical discomfort, cost, inconvenience, fatalism, fear, support and encouragement from family members are reiterated considerations [ 9 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for these improvements in diagnosis and treatment, updated studies are required using different methodologies, as conducting RCTs for the evaluation of MSPs is nowadays ethically not acceptable. Employing various methodological designs, a series of more recent international studies has shown decreased mortality and less disability for women with BC diagnosed via MSPs [10][11][12]. For Switzerland, Herrmann [7] had found a strong decline of overall BC mortality from 1992 to 2012, but, by comparing cantons with and without MSP, he did not detect signi cant regional differences as an effect of organized MSPs.…”
Section: Introductionmentioning
confidence: 99%
“…To account for these improvements in diagnosis and treatment, updated studies are required using different methodologies, as conducting RCTs for the evaluation of MSPs is ethically not acceptable. Employing various methodological designs, a series of more recent international studies has shown decreased mortality and a reduction in disability-adjusted life years for women with BC diagnosed via MSPs [ 10 12 ]. For Switzerland, Herrmann [ 7 ] found a strong decline of overall BC mortality from 1992 to 2012, but, by comparing cantons with and without MSP, he did not detect significant regional differences as an effect of organized MSPs.…”
Section: Introductionmentioning
confidence: 99%